Imam Al-Qushayri was one of the most (Journal of the College of Education for Women, 2019)
Eminent figures in Quranic studies in the fourth century of the Hegira, in hiscopacity as the founder of the essentials of the indicative approach in interpretationwhich is based on the consideration of research principles in interpretation science.Al-Qushayri participated in clarifying the promotions of this approach in hisworks which represent this approach. The mast distinguished of these works isTafseer Lataef Al-Isharat. The researcher examined the characteristics of thisapproach and its effect on the interpretative movement in Al-Qushayri age an come toemploy them as a practical example for the indicative approach in studying theinterpretation mebods in Islamic sciences.